Intervenção no Património Arquitectónico. Reflexão sobre a reabilitação do edifício Camões no Entroncamento. - Ana Rita Oliveira Fernandes (2014)
The concept of architectural heritage, which historical development has led to the inclusionof buildings beyond the monuments, carries a cultural, social, historical and artistic meaning thatreflects the identity of a community and its territory. Intervention in pre-existing buildings shouldconsider its core values and qualities, as well as the purpose of its intervention in the context of thecurrent economic situation. The decision of the most appropriate methodology - demolition,safeguard or intervention - should be underpinned by the knowledge and analysis of the preexistence,considering its historical and architectural settings, and the identification of constructive,compositional and typological elements that constitute it. Given the extension of the concept ofheritage, there has been a multiplication of attitudes and principles of intervention, which managethe confrontation between the pre-existence and its functional, infrastructural, construction andaesthetic availability.The Camões building, which is the case study of this dissertation, can through rehabilitationachieve an opportunity of functional reuse and participation in Entroncamento's socio-economicdynamics. Rehabilitating the Camões building also implies the integration of contemporaneity (inits visual and constructive dimension), and the preservation of its architectural features that carryits identity, which is considered the most viable option for a patrimonial building of public interest.